The Role of Technological Innovation in Enhancing Islamic Education Management in the Digital Era - Muhammad Wazid Husni; Moh. Solihuddin; Iqbal Ahsanul Aula; Nazih Sadatul Kahfi (Yayasan pendidikan dzurriyatul Quran, 2025)
The rapid development of digital technology has brought significant changes to the management of Islamic education, particularly in enhancing administrative efficiency, teaching quality, and stakeholder communication. This study aims to analyze how technological innovations can be applied to improve various aspects of Islamic education management and to identify the challenges and solutions involved. Employing a literature review method, the research draws on recent journal articles, books, and reports related to Islamic education and digital transformation. The results show that the use of digital-based Learning Management Systems (LMS) and Management Information Systems (MIS) has improved administrative and learning outcomes. Nevertheless, disparities in internet access and availability of devices remain pressing issues. The study concludes that comprehensive strategies, including infrastructure development, educator training, and multi-stakeholder collaboration, are essential to ensure the successful and equitable implementation of technology in Islamic education management